2018
DOI: 10.1016/j.bja.2017.11.108
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and red blood cell transfusion in intracranial neurosurgery: a comprehensive review

Abstract: Both anaemia and blood transfusion are associated with poor outcomes in the neurosurgical population. Based on the available literature, the optimal haemoglobin concentration for neurologically injured patients appears to be in the range of 9.0-10.0 g dl, although the individual risks and benefits should be weighed. Several perioperative blood conservation strategies have been used successfully in neurosurgery, including correction of anaemia and coagulopathy, use of antifibrinolytics, and intraoperative cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 69 publications
2
38
0
3
Order By: Relevance
“…our recent publication. 2 We agree with Dr. Goebel's points that transfusion of allogeneic blood is associated with increased morbidity and that the individual risks and benefits of transfusion and anaemia should be weighed before transfusion. We have emphasised these points in our discussion and conclusion.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…our recent publication. 2 We agree with Dr. Goebel's points that transfusion of allogeneic blood is associated with increased morbidity and that the individual risks and benefits of transfusion and anaemia should be weighed before transfusion. We have emphasised these points in our discussion and conclusion.…”
supporting
confidence: 55%
“…The authors concluded that further evaluation was needed with data from RCTs having low risk of bias for a definitive answer on the subject, and that the evidence of each included RCT must be interpreted with caution in the context of the individual study quality. 2 Risk of bias is associated with overestimation of benefit and underestimation of harm. 4 No single RCT was found to be at low risk of bias according to the standard of Cochrane Review Guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kisilevsky et al conducted a comprehensive review of transfusion thresholds in neurosurgical patients and recommended an optimal hemoglobin concentration of 9.0 to 10.0 g dL. 14 Smith 15 reviewed neuromonitoring in TBI and Harvey et al have provided some guidance to physicians caring for those with devastating brain injury via a consensus statement including direction on the decision to transition to palliative care. 16 Cordonnier et al have summarized the current management of acute ICH.…”
Section: Narrative Reviews Of Interestmentioning
confidence: 99%
“…Strategi-strategi diatas bukan tanpa komplikasi dan tidak semua dapat dikerjakan karena ketersediaan dan cost-effectiveness, mendorong ditelitinya efikasi dari agen-agen hemostatik seperti asam aminokaproat, asam traneksamat, desmopressin, aprotinin, serta estrogen terkonjugasi. 9,10 Asam traneksamat (trans-4-amino methyl cyclohexane carboxylic acid) merupakan golongan antifibrinolitik yang bekerja menghambat aktivasi plasminogen menjadi plasmin pada pembekuan darah.…”
Section: Pendahuluanunclassified